TRADISI NGEJOT DAPETAN PADA HARI RAYA GALUNGAN PERSPEKTIF TEOLOGI SOSIAL - Ni Made Evi Kurnia Dewi (Jnanasidanta, 2022)
The Ngejot Dapetan tradition is one of the traditions in Hinduism. The background of theresearch on the tradition of ngejot getan on Galungan Day from the perspective of social theologyis to find out the theological aspects of the tradition of ngejot getan and to know the tradition ofngejot as social harmonization in society. Research on the Tradition of Ngejot Gets on GalunganDay Social Theology Perspective is a type of qualitative research, with a theological approach,namely an approach taken to critically examine social problems related to religious issues,especially regarding the tradition of getting the ngejot. The data obtained in this study is the resultof field studies, where the primary data are Hindus who carry out the ngejot Getan tradition.Secondary data in this research is in the form of document studies or literature studies related tothe research that the researcher is studying. The Ngejot Dapetan tradition on Galungan Day is aform of actualization of Hindu religious teachings which have high theological value and are ableto create social harmonization in society.